Optimal Vessel Sizing and Understanding Dissections in Infrapopliteal Interventions: Data From the iDissection Below the Knee Study. (August 2020) - Shammas, Nicolas W.; Shammas, W. John; Jones-Miller, Susan; Torey, James T.; Armstrong, Ehrin J.; Radaideh, Qais; Shammas, Gail A.
Purpose: To investigate if imaging with intravascular ultrasound (IVUS) yields a more accurate estimate of vessel diameter and the presence of dissections than angiography after intervention in the infrapopliteal arteries. Materials and Methods: A prospective, single-center study enrolled 20 consecutive patients (mean age 74.1±12.4 years; 12 women) with infrapopliteal disease who were treated with percutaneous transluminal angioplasty (PTA; n=10) or orbital atherectomy (OA) followed by PTA (n=10). The majority of patients were hypertensive and half were diabetic. The overall lesion length was 7.3±6.3 cm, and the diameter stenosis was 80.3%±22.1%. The baseline characteristics did not differ between the groups. Vessel diameters were measured using IVUS from the internal elastic lamina (IEL) to the IEL. IVUS was performed at baseline, post PTA or OA, and post OA+PTA. Quantitative vascular angiography (QVA) and IVUS were analyzed by a core laboratory. Dissections on cine images were categorized based on the National Heart Lung and Blood Institute (NHLBI) classification, while the arc and depth were used to characterize dissections on IVUS images. Results: Mean vessel diameter by QVA was 2.9±0.6 vs 4.0±1.0 mm by IVUS according to the core laboratory (mean difference 1.1±0.9, p<0.001). On angiography, there were 7 dissections after PTA (6 C, 1 D), 1 dissection after OA (1 B), and 2 dissections after OA+PTA (1 A, 1 B; p=0.028 vs post PTA). IVUS uncovered 3.8 times more dissections than seen on angiography. There were 23 dissections after PTA (18 intima, 3 media, 2 adventitia), 12 dissections after OA (8 intima, 1 media, 3 adventitia), and 11 dissections following OA+PTA (7 intima, 1 media, 3 adventitia; p=0.425 vs PTA). Bailout stenting (all due to angiographic dissections ≥C) was necessary in 6 of the PTA cohort and none of the OA+PTA group. Conclusion: In addition to underestimating the infrapopliteal vessel diameter by 25%, angiography underappreciated the presence and severity of post-intervention dissections vs IVUS, particularly in the OA+PTA group.